The Competencies of School Administrators in the 21st Century within Hang Dong District 2 Educational Quality Development Network Schools Group under the Chiang Mai Primary Educational Service Area Office 4. - Sophon, Nareerat; Chompoonuch, Sekchai; Prasomsuk, Teerapat (MCU Haripunchai Review, 2025)
This research aimed to study 1) The Competencies of School Administrators in the 21st Century within Hang Dong District 2 Educational Quality Development Network Schools Group under the Chiang Mai Primary Educational Service Area Office 4. and 2) the guidelines for developing the competence of school administrators in the 21st century in the Hang Dong District 2 School Network for Educational Quality Development, Office of the Chiang Mai Primary Educational Service Area 4. The research design was a combination of methods. The population and samples were 107 school administrators and teachers, and 5 qualified interviewers. The research instruments were a questionnaire with a reliability of 0.95 and an interview form. Data were analyzed using percentages, means, standard deviations, and content analysis. The research results found that 1) The competence of school administrators in the 21st century in the Hang Dong District 2 School Network for Educational Quality Development, Office of the Chiang Mai Primary Educational Service Area 4 was outstanding in technology and communication, followed by self-development, teamwork, strategic planning, and leadership. In terms of change management 2) Guidelines for developing the competencies of school administrators in the 21st century, the Hang Dong District Educational Quality Development Network School Group 2 under the Office of the Primary Educational Service Area 4 Chiang Mai, found that administrators should be encouraged to study and learn the use of information technology including the application of artificial intelligence (AI) and big data in educational management. In addition, schools should be promoted to have a friendly atmosphere, be open to opinions and instill values ​​of cooperation and unity. Emphasis should be placed on studying information systems for management and effective communication with relevant personnel, as well as setting clear visions missions and strategic goals that are consistent with future trends in education and technology.